Ox-LDL increases OX40L in endothelial cells through a LOX-1-dependent mechanism - Dong,Q. (2013)
Oxidative low-density lipoprotein (Ox-LDL) is a key risk factor for the development of atherosclerosis, and it can stimulate the expression of a variety of inflammatory signals. As a new and highly sensitive inflammation index, OX40L may be a key to understanding the mechanisms that regulate interactions between cells within the vessel wall and inflammatory mediators during the development of atherosclerosis. To investigate whether Ox-LDL regulates OX40L expression through an oxidized LDL-1 receptor (LOX-1)-mediated mechanism, we investigated the effect of different concentrations of Ox-LDL (50, 100, 150 µg/mL) on endothelial cell proliferation and apoptosis. Stimulation with Ox-LDL increased OX40L protein 1.44-fold and mRNA 4.0-fold in endothelial cells, and these effects were inhibited by blocking LOX-1. These results indicate that LOX-1 plays an important role in the chronic inflammatory process in blood vessel walls. Inhibiting LOX-1 may reduce blood vessel inflammation and provide a therapeutic option to limit atherosclerosis progression.